Child Labor in Sierra Leone: Navigating the Intersection of International Law and Local Regulations - Emmanuel Allicious Macpherson Sam (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
Child labor persists as a critical issue in Sierra Leone’s diamond mining sector, where minors endure hazardous conditions contrary to international labor standards. This article delves into the complexities surrounding child labor in Sierra Leone’s diamond mines, focusing on the discord between local legislation and international regulations aimed at safeguarding children’s rights. Sierra Leone’s rich diamond reserves attract significant investment, yet the industry is marred by the exploitation of vulnerable populations, particularly children. Despite domestic laws prohibiting child labor, enforcement remains weak, and regulatory frameworks often fall short of international standards. This disconnect exacerbates the plight of children engaged in hazardous mining activities, exposing them to physical dangers and health risks and denying them access to education and a dignified childhood. The juxtaposition of Sierra Leone’s local laws with international conventions, such as the International Labour Organization’s Convention on the Worst Forms of Child Labor (Convention No. 182) and the United Nations Convention on the Rights of the Child (CRC), highlights the urgent need for harmonization and effective enforcement mechanisms. While international treaties advocate for the elimination of child labor in all its forms, including mining, implementation at the national level needs to be more cohesive and adequate. Addressing the root causes of child labor in Sierra Leone’s diamond mines necessitates a multifaceted approach. Strengthening legal frameworks, enhancing monitoring and enforcement mechanisms, and investing in education and alternative livelihoods are imperative steps towards eradicating this entrenched issue. Moreover, fostering collaboration between local authorities, industry stakeholders, and international organizations is indispensable for effecting sustainable change and protecting children’s rights in Sierra Leone’s diamond mining sector.